The Eucalyptus Cuticular Waxes Contribute in Preformed Defense Against Austropuccinia psidii - Santos, Isaneli Batista dos; Lopes, Mariana da Silva; Bini, Andressa Peres; Tschoeke, Bruno Augusto Prohmann; Verssani, Bruna Aparecida Wruck; Figueredo, Everthon Fernandes; Cataldi, Thais Regiani; Marques, João Paulo Rodrigues; Silva, Luciana Duque; Labate, Carlos Alberto; Quecine, Maria Carolina (Frontiers in Plant Science, 2019)
Autropuccinia psidii, the causal agent of myrtle rust, is a biotrophic pathogen whose growth and development depends on the host tissues. The uredospores of A. psidii infect Eucalyptus by engaging in close contact with the host surface and interacting with the leaf cuticle that provides important chemical and physical signals to trigger the infection process. In this study, the cuticular waxes of Eucalyptus spp. were analyzed to determine their composition or structure and correlation with susceptibility/resistance to Austropuccinia psidii. Twenty-one Eucalyptus spp. in the field were classified as resistant or susceptible. The resistance/susceptibility level of six Eucalyptus spp. were validated in controlled conditions using qPCR, revealing that the pathogen can germinate on the eucalyptus surface of some species without multiplying in the host. CG-TOF-MS analysis detected 26 compounds in the Eucalyptus spp. cuticle and led to the discovery of the role of hexadecanoic acid in the susceptibility of E. grandis and E. phaeotricha to A. psidii. We characterized the epicuticular wax morphology of the six previously selected Eucalyptus spp. using scanning electron microscopy and observed different behavior in A. psidii germination during host infection. In this study, we provide the first report of considerable interspecific variation in Eucalyptus spp. on the susceptibility to A. psidii and its correlation with cuticular waxes that seem to play a major role as a preformed defense mechanism.